2007
DOI: 10.1097/01.tp.0000261630.63550.41
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus Conversion in Liver Transplant Recipients With Renal Dysfunction: A Prospective, Randomized, Single-Center Trial

Abstract: This pilot trial was designed to assess the safety and efficacy of SRL in liver transplant recipients with renal dysfunction. Forty patients with renal dysfunction (24-hr CrCl 40-80 mL/min) were randomized to be withdrawn from the calcineurin inhibitor (CNI) and receive sirolimus (SRL) or to continue CNI (control arm). Improvement in 24-hour CrCl was seen in the SRL arm at 3 months (75 mL/min SRL vs. 56 mL/min control, P=0.012), whereas at 12 months there was a trend toward improvement in the SRL arm (72 mL/mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 23 publications
2
56
0
1
Order By: Relevance
“…In addition, patients switched early after transplantation may have an increased ACR risk, whereas those switching later may have already experienced additional detrimental effects on kidney function. We also acknowledge the large loading dose of sirolimus mandated by the study protocol due to the abrupt withdrawal of calcineurin inhibitor immunosuppression (10-15 mg; mean loading dose 10.3 ± 2.1 mg [range, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]), which may have impacted certain aspects of the results (e.g. TEAEs, discontinuations, etc).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, patients switched early after transplantation may have an increased ACR risk, whereas those switching later may have already experienced additional detrimental effects on kidney function. We also acknowledge the large loading dose of sirolimus mandated by the study protocol due to the abrupt withdrawal of calcineurin inhibitor immunosuppression (10-15 mg; mean loading dose 10.3 ± 2.1 mg [range, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]), which may have impacted certain aspects of the results (e.g. TEAEs, discontinuations, etc).…”
Section: Discussionmentioning
confidence: 99%
“…One randomized, single-center trial observed improvements in creatinine clearance at 3 months following CNI withdrawal and conversion to SRL, but between-group differences were not significant at 12 months (17). A second single-center trial evaluating 27 patients ≥6 months post-LT showed that patients switched to SRL had improvement in GFR after 3 (p = 0.001) and 12 months (p = 0.02) compared with those continuing CNI-based immunosuppression (18).…”
Section: Introductionmentioning
confidence: 99%
“…55,56 As regards conversion to Sirolimus in patients with CNI induced nephrotoxicity, several studies did show better GFR at 3 months following conversion to Sirolimus, but there was no difference between Sirolimus versus low dose CNI arm at 1 year. [57][58][59] Use of Sirolimus is not advised in presence of proteinuria of more than 0.8 g/ day because of risk of further worsening of renal function. 56 Also, in presence of significant kidney disease (GFR < 40 ml/min), Sirolimus may not be reno-protective and use of low dose CNI and MMF combination is probably the best strategy.…”
Section: Kidney Injury and Immunosuppressionmentioning
confidence: 99%
“…(2,15,16) A potential concern with CNI withdrawal is the risk of under-immunosuppression and ensuing rejection, which has been described in several reports (6,17). (18)(19)(20)(21)(22)(23)(24)(25)(26) (23)(24)(25)(26), concurrent non-CNI-related renal disease (25) and interval from transplantation (25,26 in which there was little improvement in the renal function of LT recipients after nonnephrotoxic drug implementation maintenance (27). …”
Section: Skin Disorders Developed In 2 Patients During the Entire Fomentioning
confidence: 99%